2010
DOI: 10.1124/jpet.110.167619
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 and D2 Receptor Mechanisms in the Abuse-Related Behavioral Effects of Cocaine: Studies with Preferential Antagonists in Squirrel Monkeys

Abstract: Dopamine (DA) D3 and D2 receptor mechanisms are implicated in cocaine's abuse-related behavioral effects, but the relative contribution of the two receptor subtypes is only partially characterized. This study investigated the role of D3 and D2 subtype mechanisms by determining the degree to which the D3-preferr- were compared. In monkeys trained to discriminate cocaine from vehicle, both DA antagonists attenuated and both DA agonists partially reproduced cocaine's DS effects. PG01037 also selectively attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 31 publications
5
58
1
Order By: Relevance
“…Seven monkeys were trained to self-administer cocaine (0.18 mg/kg/injection) by pressing a lever under a secondorder fixed-interval 5-min fixed ratio 10, FI 5 (FR10 : S), schedule of intravenous drug injection similar to the schedule described by Achat-Mendes et al (2010). Rats were similarly trained to press a lever to self-administer cocaine (0.3 mg/ kg/injection) under an FI 5 (FR5 : S) schedule.…”
Section: Cocaine Self-administration Baselinementioning
confidence: 99%
“…Seven monkeys were trained to self-administer cocaine (0.18 mg/kg/injection) by pressing a lever under a secondorder fixed-interval 5-min fixed ratio 10, FI 5 (FR10 : S), schedule of intravenous drug injection similar to the schedule described by Achat-Mendes et al (2010). Rats were similarly trained to press a lever to self-administer cocaine (0.3 mg/ kg/injection) under an FI 5 (FR5 : S) schedule.…”
Section: Cocaine Self-administration Baselinementioning
confidence: 99%
“…The dopamine D 3 receptor antagonist S33138 attenuated cocaine-enhanced brain stimulation reward and priming-induced relapse (Peng et al, 2009), and the dopamine D 3 receptor antagonist SR 21502 reduced cocaine-conditioned place preference (Hachimine et al, 2014), cue-induced relapse, and cocaine selfadministration (Galaj et al, 2014). The dopamine D 3 receptor antagonist PG01037 reduced cocaine-primed relapse in squirrel monkeys (Achat-Mendes et al, 2010), and the dopamine D 3 receptor antagonist YQA14 reduced cocaine-enhanced brain stimulation reward and attenuated cue-induced relapse (Song et al, 2014), as well as cocaine self-administration (Song et al, 2012) in rats. There is anatomic evidence for the dopamine D 3 receptor as a target also.…”
Section: Introductionmentioning
confidence: 99%
“…Both D1 and D3 receptors are expressed in mesolimbic DA projection areas. We and others have shown that D1 (Xu et al, 1994a; 1994b; 2000; Anderson et al, 2003; Bachtell et al, 2005; Alleweireldt et al, 2006; Berglind et al, 2006; Caine et al, 2007; Chen and Xu, 2010) and D3 receptors (Xu et al, 1997; Pilla et al., 1999; Vorel et al, 2002; Di Ciano et al, 2003; Neisewander et al, 2004; Xi et al, 2004; 2005; 2006; Martelle et al, 2007; Micheli and Heidbreder, 2008; Heidbreder and Newman, 2010; Achat-Mendes, et al, 2010; Chen and Xu, 2010; Kong et al, 2011; Song et al, 2012a, b) mediate locomotor-stimulant and positive reinforcing effects of cocaine, as well as cue-induced reinstatement of cocaine-seeking.…”
Section: Introductionmentioning
confidence: 95%
“…Many D3 receptor agonists and antagonists have been developed and tested and several D3 receptor antagonists show promise for attenuating reinstatement of drug-seeking in preclinical studies (Micheli and Heidbreder, 2008; Heidbreder and Newman, 2010; Newman et al, 2012). Among the many D3 receptor-preferring antagonists that have been developed and evaluated, PG01037 ( N -{4-[4-(2,3-dichlorophenyl)-piperazin-1-yl]- trans -but-2-enyl}-4-pyridine-2-yl-benzamide) selectively blocked D3-agonist induced yawning and attenuates reinstatement of drug-seeking via pharmacological antagonism of D3 receptors (Collins et al, 2005; 2007; Xi et al, 2006; Martelle et al, 2007, Achat-Mendes et al, 2010; Higley et al, 2011). We previously used both a D3 receptor mutant mouse model and PG01037 and found that D3 receptors play a key role in reconsolidation of cocaine-induced conditioned place preference (CPP) (Yan et al, 2013), implying the involvement of DA signaling in reconsolidation of cocaine memory.…”
Section: Introductionmentioning
confidence: 99%